2012
DOI: 10.1007/s13205-012-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Phytophthora colocasiae isolates in India based on AFLP analysis

Abstract: Phytophthora colocasiae that causes taro leaf blight is one of the most devastating diseases of taro which is widely distributed in India. Inter and intra-specific genetic diversity among P. colocasiae isolates collected from same field was assessed using amplified fragment length polymorphism (AFLP) marker. Seven primer pairs produced 431 markers, of which 428 (99.2 %) were polymorphic. Considerable genetic variability was displayed by the isolates. The average value of the number of observed alleles, the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Pathogens with higher genetic diversity, significant effective population size, a mixed reproduction system, and great mutation rates are assumed to possess the highest evolutionary potential ( Nath et al. 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogens with higher genetic diversity, significant effective population size, a mixed reproduction system, and great mutation rates are assumed to possess the highest evolutionary potential ( Nath et al. 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather low values for population differentiation have been reported also in other studies on molecular variation in fungi. AFLP-based studies have thus shown that 7 % of the total genetic variability occurred between populations of Fusarium pseudograminearum [12] and 14 % between populations of Phytophthora colocasiae [24] while 11 % of SNP-based variability occurred between populations of Ustilaginoidea virens [29]. Low genetic differentiation is often hypothesized to result from high levels of gene flow thus preventing geographic subdivision [15].…”
Section: Resultsmentioning
confidence: 99%
“…Genetic diversity in A.bataticola This study showed RAPD analysis, ITS sequencing and the secondary structures derived from the ITS2 sequences portray high levels of genetic variation among the isolates of A. bataticola. High levels of genetic variation has also been reported for other fungal pathogens [9,47]. A high level of genetic variation in an organism is usually explained by sexual reproduction since it creates novel recombinants.…”
Section: Secondary Structure Predictionmentioning
confidence: 98%
“…For example, reliance on fungicides may develop resistant mutants while planting with pathogen free material can lead to re-infection. The use of resistant cultivars is an important method for reducing the proliferation of plant pathogens [9]. Resistance breeding depends on understanding the genetic diversity of the pathogen in the area of production [8].…”
Section: Introductionmentioning
confidence: 99%